Application of Tilawatil Qur'an Method to Improve the Ability Reading Al-Qur'an in Bahrul Ulum Islamic Boarding School - Dian Kusuma Wardani; M Salma Nuur Samsu (SCHOOLAR: Social and Literature Study in Education, 2022)
Tilawatil Quran is a form of dhikr to Allah SWT and is the most important form of worship that Rasulallah has made as the greatest worship for a means of getting closer to Allah. This study aims to determine the forms of the Tilawatil Quran method in Bahrul Ulum (Induk) Tambakberas Jombang Islamic Boarding School. This research is qualitative descriptive. Data collection through observation, interviews and documentation, data obtained during the study were analyzed by reducing data. Presenting data, and drawing conclusions from the results of these studies. The result of the research is that there are student lines that form the letter U, 2- banjars, 2- shaff, clustered and others. The teacher reads out then the students imitate, some immediately come forward to be listened to by the teacher, some read together at the same time the teacher listens to, and so on. The development of students after following various forms of the Tilawatil Quran method is that the average reading becomes more fluent, understanding tajwid, makharijul letters, character traits, and many more. The conclusion of the research is the form of the Tilawatil Qur'an method is different and the development of the students after following various forms of the tilawatil Qur'an method is basically better than before both in terms of reading, tajwid understanding and others.